Analisis Pengaruh Kepercayaan, Keamanan, dan Kualitas yang Dirasakan terhadap Keputusan Pembelian Produk di Aplikasi Shopee - Aulia, Tasfiyah; Ronny, Ronny (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2024)
In the current era of digital development, the development of internet technology is so rapid. This changes the way of view, the way of working, and all fields including in terms of online shopping. This study aimed to examine the influence of trust, safety, and perceived quality on purchasing decisions. The sample consisted of 129 respondents, namely Shopee customers who have characteristics of at least 19 years and have purchases at Shopee. This study used Structural Equating Modeling (SEM) analysis on Partial Least Square (PLS) and used questionnaire distribution in the form of google form for data collection. The results of this study show that there is a significant positive influence of trust on purchasing decisions. This research shows a significant positive influence of security on purchasing decisions. The latest result of this study is that perceived quality also has a significant positive effect on purchasing decisions.